Making Offline and Online Work Procedures for Vision Glasses Optical Store in Surabaya - Jacqueline Bernessa Kuncoro (Institute of Research and Community Outreach - Petra Christian University, 2023)
Vision Glasses is a Surabaya-based eyewear shop selling high-quality, affordable glasses, lenses, and eyewear accessories. This thesis intends to discuss the existing managerial issue in Vision Glasses, namely work performance. This research employs theory of constraints and the theory of work procedure by Boutros & Purdie. After collecting the data from the owner and employees of Vision Glasses, the writer discovers that Vision Glasses needs to apply a work procedure which contains rules or guidelines such as the policy, customer-service ethics, and division instructions for the employees and as a guideline for the company to discipline the employees or deal with internal conflict.